Canada : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper assesses the impact of high household debt on economic volatility in Canada. The debt per se may not necessarily be a risk for economic activity; it can amplify other shocks as well. A few studies have emphasized the link between the growth of household debt before 2007 and the severity of the Great Recession. Economies with debt tend to experience more severe housing busts and recessions. If household debt ratios are not stabilized, the vulnerability of the Canadian economy is likely to be high.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet